2010
DOI: 10.1161/atvbaha.109.201079
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H1 Receptor Promotes Atherosclerotic Lesion Formation by Increasing Vascular Permeability for Low-Density Lipoproteins

Abstract: Objective-Enhanced endothelial permeability leading to intimal accumulation of low-density lipoproteins (LDL) stimulates the formation of atherosclerotic lesions. Histamine is known to increase vascular permeability. Whether this affects the formation of atherosclerotic lesions, however, remains elusive. Methods and Results-Apolipoprotein E-null (ApoE Ϫ/Ϫ ) mice treated with a histamine H1 receptor but not an H2 receptor antagonist developed 40% fewer atherosclerotic lesions in the aorta than placebo-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 33 publications
1
51
3
1
Order By: Relevance
“…Under these experimental conditions, the stimulatory effect of histamine on m-RCT appeared to be mediated mainly by the H1R, with the H2R exerting a small additive effect. Consistent with our fi ndings, activation of H1R, rather than H2R, has been found to enhance vascular permeability for endogenous LDL in cholesterol-fed apoE Ϫ / Ϫ mice without altering the plasma lipoprotein levels ( 34 ). It has been also shown that histamine increases the passage of LDL through monolayers of human arterial endothelial cells, having its peak at 2 h but rapidly decreasing to the control level within 4-6 h, and, moreover, that this effect can be blocked by the H1R antagonist pyrilamine, rather than by the H2R antagonist cimetidine ( 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…Under these experimental conditions, the stimulatory effect of histamine on m-RCT appeared to be mediated mainly by the H1R, with the H2R exerting a small additive effect. Consistent with our fi ndings, activation of H1R, rather than H2R, has been found to enhance vascular permeability for endogenous LDL in cholesterol-fed apoE Ϫ / Ϫ mice without altering the plasma lipoprotein levels ( 34 ). It has been also shown that histamine increases the passage of LDL through monolayers of human arterial endothelial cells, having its peak at 2 h but rapidly decreasing to the control level within 4-6 h, and, moreover, that this effect can be blocked by the H1R antagonist pyrilamine, rather than by the H2R antagonist cimetidine ( 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, no effect on atherosclerosis was seen with HRH2 KO or an H2 antagonist (ranitidine) (1515).…”
Section: Mast Cells In Atherosclerosismentioning
confidence: 85%
“…Ϫ/Ϫ bone marrow did not affect atherosclerosis (1515). In contrast, no effect on atherosclerosis was seen with HRH2 KO or an H2 antagonist (ranitidine) (1515).…”
Section: Mast Cells In Atherosclerosismentioning
confidence: 87%
See 1 more Smart Citation
“…The antagonists of histamine receptor 1 (H 1 ) abolish the effect of histamine and reduce the formation of intimal hyperplasia (14). Recently, it has been reported that histamine H 1 receptor promotes the development of atherosclerotic lesions by increasing vascular permeability for low-density lipoprotein (LDL) (19).…”
mentioning
confidence: 99%